2017
DOI: 10.1016/j.molcel.2017.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a Thermostable Group II Intron Reverse Transcriptase with Template-Primer and Its Functional and Evolutionary Implications

Abstract: SUMMARY Bacterial group II intron reverse transcriptases (RTs) function in both intron mobility and RNA splicing and are evolutionary predecessors of retrotransposon, telomerase, and retroviral RTs, as well as spliceosomal protein Prp8 in eukaryotes. Here, we determined a crystal structure of a full-length thermostable group II intron RT in complex with an RNA template-DNA primer duplex and incoming dNTP at 3.0-Å resolution. We find that the binding of template-primer and key aspects of the RT active site are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
123
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(131 citation statements)
references
References 46 publications
1
123
0
Order By: Relevance
“…Thermostable group II intron RTs (TGIRTs) from bacterial thermophiles combine these beneficial properties with the ability to function at high temperatures (60-65 ο C), which help melt out stable RNA secondary structures that can impede reverse transcription (Mohr et al 2013). A recent crystal structure of a full-length TGIRT enzyme (GsI-IIC RT, a form of which is sold commercially as TGIRT-III; InGex) in active conformation with bound substrates revealed that group II intron RTs are closely related to RNA-dependent RNA polymerases, as expected for an ancestral RT, and identified a series of novel structural features that may contribute to their high fidelity and processivity (Stamos et al 2017). These features include more constrained binding pockets than retroviral RTs for the templating RNA base, 3' end of the DNA primer, and the incoming dNTP, as well as a larger fingers region that enables more extensive contact with the template-primer substrate than is possible for retroviral RTs (Stamos et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Thermostable group II intron RTs (TGIRTs) from bacterial thermophiles combine these beneficial properties with the ability to function at high temperatures (60-65 ο C), which help melt out stable RNA secondary structures that can impede reverse transcription (Mohr et al 2013). A recent crystal structure of a full-length TGIRT enzyme (GsI-IIC RT, a form of which is sold commercially as TGIRT-III; InGex) in active conformation with bound substrates revealed that group II intron RTs are closely related to RNA-dependent RNA polymerases, as expected for an ancestral RT, and identified a series of novel structural features that may contribute to their high fidelity and processivity (Stamos et al 2017). These features include more constrained binding pockets than retroviral RTs for the templating RNA base, 3' end of the DNA primer, and the incoming dNTP, as well as a larger fingers region that enables more extensive contact with the template-primer substrate than is possible for retroviral RTs (Stamos et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This difference may reflect that template-switching by retroviral RTs involves partial or complete dissociation of the enzyme from the initial template, enabling the completed cDNA to base pair to the new template for reinitiation of cDNA synthesis by the same or another RT. By contrast, non-LTR-retroelement RTs bind the donor and acceptor simultaneously without dissociating, leaving a relatively small binding pocket that may sterically hinder access to multiple overhang bases (41).…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of GsI-IIC RT to other non-LTR-retroelement RTs. Non-LTR-retroelement RTs typically have an NTE with a conserved RT0 motif that likely contributes to a structurally similar binding pocket for the 3' end of the acceptor nucleic acid during template switching (5,19,41,42). Thus, it is unsurprising that many features of the template switching and NTA mechanisms of Gs-IIC RT are similar to those found previously for the MRP and R2 element RTs, including a prominent role for NTA in adding nucleotides to the 3' end of the cDNA that can base pair to the 3' end of acceptor RNAs (25,33,34).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations